COVER DEPAN, SUSUNAN REDAKSI, DAFTAR ISI - Indonesian Journal of Aquaculture Medium; Jurnal Media Akuakultur Indonesia (Jurnal Media Akuakultur Indonesia, 2022)
Indonesian Journal Of Aquaculture Medium Volume 2, Number 1, June 2022